2018
DOI: 10.1111/aogs.13328
|View full text |Cite
|
Sign up to set email alerts
|

Medical treatment in the management of deep endometriosis infiltrating the proximal rectum and sigmoid colon: a comprehensive literature review

Abstract: A comprehensive literature review was performed to evaluate the effect of various hormonal therapies, in terms of variations of intestinal and pain complaints and of patient satisfaction with treatment, in women with symptomatic, non-severely sub-occlusive endometriosis infiltrating the proximal rectum and sigmoid colon. A MEDLINE search through PubMed from 2000 to 2018 was conducted to identify all original English language articles published on medical treatment for colorectal endometriosis. Additional repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 59 publications
(141 reference statements)
0
12
1
3
Order By: Relevance
“…It has been previously reported that hormonal therapies can decrease the size of deep endometriotic nodules [18,30]; however, it seems that there is no direct correlation between improvement of symptoms and decrease in nodule volume [30]. In our study, at the end of follow-up visits under DNG therapy, a mean nodule volume reduction of at least 10% was reported by around 30% of women.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…It has been previously reported that hormonal therapies can decrease the size of deep endometriotic nodules [18,30]; however, it seems that there is no direct correlation between improvement of symptoms and decrease in nodule volume [30]. In our study, at the end of follow-up visits under DNG therapy, a mean nodule volume reduction of at least 10% was reported by around 30% of women.…”
Section: Discussioncontrasting
confidence: 65%
“…The diagnosis of rectosigmoid endometriosis was based on transvaginal ultrasonography (TVS). Only women with endometriotic nodules infiltrating at least the muscular layer of the rectal wall and with an estimated stenosis of the bowel lumen <60% were considered eligible to be treated by hormonal therapy, as previously suggested [18]. Although some of the patients included in the study had previously undergone laparoscopy for endometriosis, none of them had previous bowel surgery (with the exception of appendectomy).…”
Section: Study Populationmentioning
confidence: 99%
“…Probably due to local anatomical and physiological factors, endometriotic lesions of the left colon are much more frequent than those infiltrating the right colon [2]. Left lesions comprise those involving the rectosigmoid junction (proximal rectum plus distal sigmoid) and those above the rectosigmoid junction (nodules of the mid-and proximal sigmoid) [19,20]. Right infiltrating lesions generally involve the terminal ileum and the cecum.…”
Section: Anatomical and Histological Premisesmentioning
confidence: 99%
“…Decreased libido (19) Vaginal dryness (12) At Spotting (11) Breast tenderness (6) Bloating 5Headache 4Depression 4Nausea ( Weight gain (16) Spotting (13) Decreased libido (9) Vaginal dryness 7Bloating (6) Similar satisfaction with treatment and pain relief. Alopecia 5Headache 3Mood disorders (2) Breast tenderness 1Nausea 1Breakthrough bleeding…”
Section: Sourcementioning
confidence: 99%
“…In cases in which medical treatment fails, surgical resection either by discoid resection (DR) or segmental resection (SR) is often the treatment of choice. Surgical treatment of DE affecting the rectosigmoid has been shown to decrease pain, and may be beneficial for fertility [3][4][5][6][7] . Transvaginal sonography (TVS) is a cost-effective, highly accurate and non-invasive tool that is regarded as the first line technique in assessing women with endometriosis, especially when DE is suspected [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%